Orchard microclimate, tree water uptake and sweet cherry fruit quality under protected cropping - Stone, Cameron Hugh; Close, Dugald C.; Bound, Sally A.; Corkrey, Ross (Frontiers in Plant Science, 2022)
Protected cropping systems (PCS) de-risk adverse climatic effects in intensive horticultural production but alter the growing environment. The objectives of this study were to investigate the effects of modern PCS on sweet cherry orchard microclimate, tree water uptake and fruit quality. Sap flow sensors and weather stations were positioned at four locations under a 21 ha PCS at varying elevations (125, 114, 111, 102 m above sea level) and distances from the PCS boundary (105, 75, 60 or 50 m, referred to hereafter as Locations 1 to 4, respectively). Generalised additive models (GAMs) were used to predict individual climate parameters (temperature, relative humidity (RH), solar radiation and wind speed) on tree sap flow at each of the locations. Average and maximum temperatures and average minimum RH were higher (15.9°C, 26.1°C and 49.0%) at locations with higher elevations and located further from the PCS boundary (1 and 2) in contrast to locations at lower elevations and closer proximity to the PCS boundary (3 and 4) (15.4°C, 24.6°C and 48.1%). Predicted sap flow was strongly correlated (r2 = 0.92) with time across the four locations under the PCS. GAMS modelling indicated that the hourly water uptake by trees within close proximity to the block boundary (3 and 4) responded with greater intensity to increases in temperature and reductions in RH, taking up on average 0.15 L h-1 (at temperatures >30°C) and 0.08 L h-1 (at RH <50%), respectively, in contrast to trees further under the PCS (1 and 2) where average tree water uptake was 0.08 and 0.04 L h-1 at temperatures >30°C and RH <50%, respectively. Highest predicted hourly tree sap flow was associated with high wind speeds (0.67 L h-1) and low RH levels (0.61 L h-1). Fruit harvested from locations further from the PCS boundary had significantly higher dry matter content (18.2%), total soluble solids (17.8%) and compression firmness (311.3 g mm-1) in contrast to fruit closer to the PCS boundaries (16.1%, 15.7% and 258.3 g mm-1). This study provides greater understanding of the effects of PCS on microclimate and consequences for tree water uptake and fruit quality.